Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2009)
The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point; however, the lesions caused by B. corticola were longer in both oak species. On cork oak seedlings, all pathogens induced a signiﬁcant and gradual reduction in net photosynthesis and stomatal conductance values, whereas other physiological disturbances were induced only by B. corticola infections on holm oak seedlings.
Keywords: Cork oak; fungal pathogens; Holm oak; physiological responses (voyant); seedlings

Ontogenetic changes in stomatal and biochemical limitations to photosynthesis of two co-occurring Mediterranean oaks differing in leaf life span - Juárez-López, Francisco José; Escudero, Alfonso; Mediavilla, Sonia (Tree Physiology, 2008)
A quantitative analysis was applied to the stomatal and biochemical limitations to light-saturated net photosynthesis under optimal field conditions in mature trees and seedlings of the co-occurring evergreen oak, Quercus ilex L., and the deciduous oak, Q. faginea Lam. Stomatal limitation to photosynthesis, maximal Rubisco activity and electron transport rate were determined from assimilation versus intercellular leaf carbon dioxide concentration response curves of leaves that were subsequently analyzed for nitrogen (N) concentration, mass per unit area, thickness and percent internal air space. In both species, seedlings had a lower leaf mass per unit area, thickness and leaf N concentration than mature trees. The root system of seedlings during their third year after planting was dominated by a taproot. A lower leaf N concentration of seedlings was associated with lower maximal Rubisco activity and electron transport rate and with assimilation rates similar to or lower than those of mature trees, despite the higher stomatal conductances and potential photosynthetic nitrogen-use efficiencies of seedlings. Consequently, stomatal limitation to photosynthesis increased with tree age in both species. In both seedlings and mature trees, a lower assimilation rate in Q. ilex than in Q. faginea was associated with lower stomatal conductance, N allocation to photosynthetic functions, maximal Rubisco activity and electron transport rate, and potential photosynthetic nitrogen-use efficiency but greater leaf thickness and leaf mass per unit area. Tree-age-related changes differed quantitatively between species, and the characteristics of the two species were more similar in seedlings than in mature trees. Despite higher stomatal conductances, seedlings are more N limited than adult trees, which contributes to lower biochemical efficiency.
10.1093/treephys/28.3.367
Keywords: A–ci response curves; biochemical capacity; leaf morphology; leaf N allocation; mature trees; Quercus faginea; Quercus ilex; seedlings; Stomatal conductance

Root responses of Quercus ilex L. seedlings to drought and fire - Chiatante, D; Di Iorio, A; Scippa, G S (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Drought treatments in holm-oak (Quercus ilex) seedlings induce variations in total root length, number of root apices, shoot/root dry weight, and root electrolyte leakage. When drought treatments last for more than 50 days a considerable number of fine lateral roots die, irrespective of branching order or distribution within the root system. Scorching of drought-treated seedlings induces a transient stimulation of root growth. These results indicate that root turnover is deeply affected during treatments, with survival of seedlings being entrusted to the tolerance of a number of roots situated in the deeper region of the root system. Activity of the meristematic tissue present within the apices of these surviving roots supports regeneration of above-ground lost organs during recovery. Knowledge of the mechanisms ensuring the survival of Mediterranean tree seedlings following drought and fire is useful for developing models of vegetation dynamics.
doi: 10.1080/11263500500160591
Keywords: Drought; Quercus ilex; root system; seedlings; ﬁre

Root responses of Quercus ilex L. seedlings to drought and fire - Chiatante, D.; Di Iorio, A.; Scippa, G. S. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Drought treatments in holm-oak (Quercus ilex) seedlings induce variations in total root length, number of root apices, shoot/root dry weight, and root electrolyte leakage. When drought treatments last for more than 50 days a considerable number of fine lateral roots die, irrespective of branching order or distribution within the root system. Scorching of drought-treated seedlings induces a transient stimulation of root growth. These results indicate that root turnover is deeply affected during treatments, with survival of seedlings being entrusted to the tolerance of a number of roots situated in the deeper region of the root system. Activity of the meristematic tissue present within the apices of these surviving roots supports regeneration of above-ground lost organs during recovery. Knowledge of the mechanisms ensuring the survival of Mediterranean tree seedlings following drought and fire is useful for developing models of vegetation dynamics.
doi: 10.1080/11263500500160591doi: 10.1080/11263500500160591The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Drought; Quercus ilex; root system; seedlings; ﬁre

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M; Royo, A; Gil, L; Pardos, J A (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M.; Royo, A.; Gil, L.; Pardos, J. A. (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.6710.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)

BIRD-DISPERSED SEED RAIN AND SEEDLING ESTABLISHMENT IN PATCHY MEDITERRANEAN VEGETATION - Debussche, M.; Isenmann, P. (OIKOS, 1994)
The composition and spatial patterns of the seed rain produced by bird dispersers and of the seedlings of fleshy-fruited plants have been studied in patchy Mediterranean vegetation in southern France. The seeds of fleshy-fruited plants were collected in seed traps during a 17-month period (1981-1983) and the fecal samples of bird dispersers mist-netted on the same 2.5-ha site over a 25-month period (1981-1984) were analysed. The locations of the 5 sets of seed traps and the 6 mist-nets were chosen in order to take into account the various plant communities and the successional gradient from old fields to Quercus ilex coppice. Seedling establishment of fleshy-fruited plants was censused in 1983 adjacent to the seed traps. In 1992 seedlings were again censused in the open coppice and in the old fields. The seeds of 38 fleshy-fruited plants were collected, including 13 alien and cultivated species. Among them, 25 species were dispersed by Sylvia atricapilla, which dispersed the most diverse and mixed seed rain of the various bird dispersers. Species richness of the seed rain increased log-linearly with seed density, ranging from 3 to 21 species per 0.25 m2. Seed density was very heterogeneous in space. The maximum density of seeds was observed under the canopy of isolated trees and saplings in the old fields (up to 829 per 0.25 m2) which are the favoured perching places for the dispersers. Minimum density was observed in the same old fields outside the canopy of these same trees and saplings (down to 12 per 0.25 m2). In the Quercus ilex coppice, the higher the canopy, the higher the seed density. Dispersal was a short distance process. A large majority of the seeds of Pyracantha coccinea and Sambucus nigra were dispersed by birds less than 100 m from the maternal plant. However, a dispersal distance of > 300 m was observed for a seed of Ligustrum vulgare, In 1983 the < 1 yr-old seedlings of 17 fleshy-fruited plants, including only one alien species, and the 1-2 yr-old seedlings of 7 native species were censused. Though important components of the seed rain, no 1-2 yr-old seedlings of several alien (e.g. Pyracantha coccinea) or native (e.g. Rhus coriaria) species were observed in the studied vegetation. Seedlings were more numerous under tree cover than in the coppice clearings. In the old fields, < 1 yr-old seedlings were more numerous under the canopy than in open areas. No such difference was observed under saplings in 1983 and very few seedlings were observed in the old fields. The 1992 census suggested that the positive role of the cover of pioneer plants on seedling establishment progressively increased with successional development. This is probably due to an increase in the nurse effect and a decrease in the herbaceous cover under the canopy. It is suggested that. in old fields. the establishment of fleshy-fruited plants is favoured when seeds are deposited under pioneer woody plants rather than in open areas. The bird dispersers thus trigger dynamic processes initiated by the pioneer woody plants in Mediterranean old field succession. More generally, dispersal of fleshy-fruited plants by birds is more significant in the central stages of succession gradient than it is in open herbaceous communities and in dense forest when both have an homogeneous structure.
APSAPSThe following values have no corresponding Zotero field: pub-location: 35 NORRE SOGADE, PO BOX 2148, DK-1016 COPENHAGEN, DENMARK publisher: MUNKSGAARD INT PUBL LTD
Keywords: bird dispersers; fleshy-fruited; France; Mediterranean; Quercus ilex; seedlings